+0  
 
0
177
1
avatar+2509 

Help.

NotSoSmart  Dec 7, 2017
 #1
avatar+87639 
+1

y =  ( x - 12)^3 - 7

 

(x - 12)^3 - 7  = 0     add 7 to both sides

 

(x - 12)^3  = 7        take the cube root of both sides

 

x  - 12  = ∛7        add 12 to both sides

 

x  = ∛7  + 12

 

 

cool cool cool

CPhill  Dec 7, 2017

11 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.